Los métodos modernos y las regularidades de los principios del arte pictórico - Derbisova, Mariya; Myrzakhmetova, Saltahat; Nigmetova, Ardak; Krykbayeva, Sara (Innovaciencia, 2022)
Introduction: The teaching of this discipline in the system of education of designers requires the introduction of new modern developments into the educational process. The subjects of general artistic training play an essential role in the training of designers. Materials and Methods: The article discusses the patterns of painting, the development of which forms the student’s pictorial knowledge, skills and abilities, and the possession of various methods of pictorial representation develops creative individuality and artistic taste, which is necessary in the further professional activity of the designer. Results and Discussion: An important task in the artistic training of designers is to teach them how to work with artistic means and materials used in professional design activities. These skills can be mastered in the process of studying the course of painting. Conclusions: A professional approach to studying the issues of technique and technology of mastering painting materials and means improves the quality of a designer’s creative training.